2019
DOI: 10.1016/j.bbrc.2019.03.199
|View full text |Cite
|
Sign up to set email alerts
|

The NADase CD38 is induced by factors secreted from senescent cells providing a potential link between senescence and age-related cellular NAD+ decline

Abstract: Tissue nicotinamide adenine dinucleotide (NAD+) decline has been implicated in aging. We have recently identified CD38 as a central regulator involved in tissue NAD+ decline during the aging process. CD38 is an ecto-enzyme highly expressed in endothelial and inflammatory cells. To date, the mechanisms that regulate CD38 expression in aging tissues characterized by the presence of senescent cells is not completely understood. Cellular senescence has been described as a hallmark of the aging process and these ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 36 publications
2
93
0
Order By: Relevance
“…Low levels of NAD + were also reported in several tissues (Massudi et al, 2012;Zhu et al, 2015), and supplementation of NAD + precursors increased life span in different species (Fang et al, 2016;Zhang et al, 2016). Interestingly, SCs were shown to induce the SASP-mediated expression of CD38 -an ectoenzyme with a high NADase activity -in non-senescent cells, such as endothelial cells and bone marrow-derived macrophages (Chini et al, 2019;Covarrubias et al, 2019). CD38 inhibitors rescued NAD + decline and ameliorated a number of age-related metabolic outcomes in mice (Tarrago et al, 2018).…”
Section: Me1mentioning
confidence: 93%
“…Low levels of NAD + were also reported in several tissues (Massudi et al, 2012;Zhu et al, 2015), and supplementation of NAD + precursors increased life span in different species (Fang et al, 2016;Zhang et al, 2016). Interestingly, SCs were shown to induce the SASP-mediated expression of CD38 -an ectoenzyme with a high NADase activity -in non-senescent cells, such as endothelial cells and bone marrow-derived macrophages (Chini et al, 2019;Covarrubias et al, 2019). CD38 inhibitors rescued NAD + decline and ameliorated a number of age-related metabolic outcomes in mice (Tarrago et al, 2018).…”
Section: Me1mentioning
confidence: 93%
“…The mechanisms that underlie NAD + level decrease remain a fundamental question. A recent report from Chini et al 19 suggests that SASP from senescent cells can induce CD38 in endothelial cells and bone marrow-derived macrophages. CD38 is a major consumer of NAD + .…”
Section: Senescent State Can Reduce Nad +mentioning
confidence: 99%
“…CD38 expression was recently found to be driven by a cocktail of cytokines and chemokines secreted by senescent cells. Cellular senescence is a cell fate in which cells cease to divide and adopt a senescent-associated secretory phenotype (SASP) characterized by the secretion of factors (including proinflammatory cytokines and chemokines) that promote chronic "sterile" inflammation and fibrosis [68]. Several studies found that senescent cells accumulate with age, including in the brain [69].…”
Section: Aging the Missing Link Between Cd38 And Neurodegeneration/imentioning
confidence: 99%